Sebaran dan Keterjangkauan Rumah Sakit Rujukan COVID-19 di Kota Depok - Aldila Riznawati; Ratih Trivalni; Martya Rahmaniati (FORIKES, 2023)
The surge in cases of patients confirmed positive for COVID-19 has prompted the Indonesian government to designate several hospitals as referral hospitals for COVID-19 patients. Depok City, which is the area with the highest positive COVID-19 cases in West Java Province in 2021, has 21 referral hospitals spread across several sub-district areas. Therefore, it is necessary to carry out this research which aimed to determine the distribution and reach of health services at the COVID-19 referral hospital in Depok City by utilizing a geographic information system application. To see the distribution and affordability of health services at COVID-19 referral hospitals, mapping was carried out using buffer, overlay and intersection analysis based on the road network and hospital coverage radius. The mapping results showed that the distribution of hospital locations was not evenly distributed and tends to be concentrated in several sub-district areas and the area of health service affordability was within a medium to long radius, using a service coverage standard of 3 kilometers from the road network to the referral hospital. It was concluded that hospital facilities were not evenly distributed in Depok City, so it was necessary to plan the development of hospital infrastructure with priority locations in sub-district areas that did not yet have hospitals.Keywords: Covid-19; referral hospital; distribution; affordability ABSTRAK Melonjaknya kasus pasien terkonfirmasi positif COVID-19 membuat pemerintah Indonesia menunjuk beberapa rumah sakit sebagai rumah sakit rujukan untuk pasien COVID-19. Kota Depok yang merupakan wilayah dengan kasus COVID-19 positif tertinggi di Provinsi Jawa Barat tahun 2021 memiliki 21 rumah sakit rujukan yang tersebar di beberapa wilayah kecamatan. Oleh karena perlu dilakukan penelitian ini yang bertujuan untuk mengetahui sebaran dan jangkauan pelayanan kesehatan RS rujukan COVID-19 di Kota Depok dengan memanfaatkan aplikasi sistem informasi geografis. Untuk melihat sebaran dan keterjangkauan pelayanan kesehatan RS rujukan COVID-19 dilakukan pemetaan dengan analisis buffer, overlay dan intersection berdasarkan jaringan jalan dan radius jangkauan RS. Hasil pemetaan menunjukkan sebaran lokasi rumah sakit yang belum merata dan cenderung terpusat di beberapa wilayah kecamatan dan area keterjangkauan pelayanan kesehatan berada dalam radius sedang hingga jauh, dengan menggunakan standar jangkauan pelayanan 3 kilometer jarak dari jaringan jalan ke rumah sakit rujukan. Disimpulkan bahwa belum meratanya fasilitas rumah sakit di Kota Depok sehingga diperlukan perencanaan pembangunan infrastruktur rumah sakit dengan prioritas lokasi wilayah kecamatan yang belum memiliki rumah sakit. Kata kunci: Covid-19; rumah sakit rujukan; sebaran; keterjangkauan